18F-FES radiation dosimetry preliminary estimates for preclinical studies based on voxelized phantom - Andréa Vidal Ferreira; Ana Carolina Araujo Bispo; Christiane Silva Leite; Juliana Batista da Silva; Marcelo Mamede; Rodrigo Modesto Gadelha Gontijo; Bruno Melo Mendes (Brazilian Journal of Radiation Sciences)
Small animals, such as mice, are used in radiopharmaceutical biodistribution studies and innumerous others preclinical investigations involving ionizing radiation. Longitudinal preclinical studies with five or more image procedures, involving radiopharmaceuticals injection and/or X-radiation, are not uncommon. However, a suitable dosimetric evaluation is not always available and, sometimes, absorbed doses in animal organs or tissues and their influence in experimental results were not appropriately taken into account. Accurate calculation of absorbed doses in mice organs are needed to evaluate potential radiobiological effects that may interfere with in vivo experiments. In this work, we perform a preliminary 16α-[18F]-fluoro-17β-estradiol (18F-FES) radiation dosimetry estimates for female mice. The obtained animal dosimetric results can be useful for evaluating animal doses during the design of longitudinal preclinical studies.